2010
DOI: 10.1083/jcb.200910021
|View full text |Cite
|
Sign up to set email alerts
|

LGN regulates mitotic spindle orientation during epithelial morphogenesis

Abstract: Abbreviations used in this paper: aPKC, atypical protein kinase C; Crb3, Crumbs3; G, the alpha subunit of the heterotrimeric G proteins; Gi, the alpha subunit of adenylyl cyclase-inhibitory heterotrimeric G proteins; GoLoco motif, G i/o -Loco motif; LGN, mammalian homologue of Pins; MT, microtubule; NuMA, nuclear mitotic apparatus protein; Pins, partner of inscuteable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
216
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(244 citation statements)
references
References 55 publications
(98 reference statements)
28
216
0
Order By: Relevance
“…7A). Orientation of cell division is an early sign of polarization, and previous work has shown that recruitment of a complex comprising NuMA and LGN (also known as GPSM2) to the lateral cortex is required for cell orientation during mitoses in both chick neuroepithelium in vivo and MDCK cells in vitro (Peyre et al, 2011;Zheng et al, 2010). Further, the NuMA-LGN complex recruits Par1b to define lumen position (Lázaro-Diéguez et al, 2013).…”
Section: δU5-gukmentioning
confidence: 99%
See 1 more Smart Citation
“…7A). Orientation of cell division is an early sign of polarization, and previous work has shown that recruitment of a complex comprising NuMA and LGN (also known as GPSM2) to the lateral cortex is required for cell orientation during mitoses in both chick neuroepithelium in vivo and MDCK cells in vitro (Peyre et al, 2011;Zheng et al, 2010). Further, the NuMA-LGN complex recruits Par1b to define lumen position (Lázaro-Diéguez et al, 2013).…”
Section: δU5-gukmentioning
confidence: 99%
“…8A,B). Because previous studies have linked defective mitotic spindle orientation directly to the multi-lumen phenotype (Durgan et al, 2011;Hao et al, 2010;Jaffe et al, 2008;Qin et al, 2010;Rodriguez-Fraticelli et al, 2010;Xia et al, 2015;Zheng et al, 2010), we relied on the strong phenotype of single-versus multi-lumen cyst formation as both a morphogenetic indicator and marker of early polarization processes -e.g. spindle orientation.…”
Section: Full-length But Not Zo-1-binding Defective Occludin Restormentioning
confidence: 99%
“…Using a quantitative mass-spectrometry approach as a starting point, LIN-5 was found to be phosphorylated by PKC-3; such phosphorylation negatively regulates LIN-5 function and thus contributes to lowering pulling forces on the embryo anterior [50]. In mammalian cells, atypical protein kinase C phosphorylates LGN, causing its loss from the apical cortex in polarized MDCK cells, thereby perturbing spindle positioning [51,52]. Studies in human cells have led to the identification of two other kinases involved in spindle positioning, ABL1 (Abelson kinase1) and PLK1 (Polo-like kinase1).…”
Section: Cortical Dynein: a Force-generating Motormentioning
confidence: 99%
“…The Gai complex also partakes in planar epithelial divisions of epithelial monolayers. [47][48][49] In this case, the Gai complex recruits Dynein-dynactin to the lateral cortex, which pull spindle poles toward the lateral side of the dividing cells. In certain cell types aPKC plays an active role excluding LGN from the apical domain and restricting it to the lateral cortex.…”
Section: Cell Polarity and Polarized Cell Divisionsmentioning
confidence: 99%